PAH and H2 emission in the Ring Nebula. Issue 3 (July 2016) - Cox, N L J; Pilleri, P; Berné, O; Cernicharo, J; Joblin, C
Abstract: This paper presents the Spitzer IRS (Infra Red Spectrograph) detection of mid-infrared polycyclic aromatic hydrocarbon (PAH) emission features and H2 associated with dense knots in the ring of the "oxygen-rich" (C/O∼⃒0.6-0.8) planetary nebula (PN) NGC6720 (Ring Nebula). We explored a further three oxygen-rich extended PNe with similar dataset available. These turned out to be non-detection of PAHs, although two of these do contain H2 emission knots. The presence of PAHs is discussed in the context of a bottom-up formation mechanism, in which first small hydrocarbons, and later PAHs, are formed in warm dense knots inside the ionised regions of PNe.